2020
DOI: 10.1055/s-0040-1715709
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Effect of Prone Positioning Methods on Blood Loss and Intra-Abdominal Pressure in Obese Patients Undergoing Spinal Surgery

Abstract: Background Improper prone positioning of obese patients for spine surgery can increase the intra-abdominal pressure (IAP), resulting in increased bleeding from epidural venous plexus. The choice of prone positioning frame can be an important determinant of the IAP. Materials and Methods This prospective, randomized study was performed on obese patients (body mass index ≥ 30) scheduled for lumbar laminectomy. After administration of general anesthesia, patients were positioned prone either on Wilson’s frame (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Pads should be far enough apart and lowered in order to decrease intra-abdominal pressure and restore lordosis. A recent study reported that a horizontal bolster could be an alternative to the four-poster frame by decreasing intra-abdominal pressure and blood loss more than the Wilson frame can [19]. Furthermore, hip extension can increase lumbar lordosis.…”
Section: Suggestions About Patient Positioningmentioning
confidence: 99%
“…Pads should be far enough apart and lowered in order to decrease intra-abdominal pressure and restore lordosis. A recent study reported that a horizontal bolster could be an alternative to the four-poster frame by decreasing intra-abdominal pressure and blood loss more than the Wilson frame can [19]. Furthermore, hip extension can increase lumbar lordosis.…”
Section: Suggestions About Patient Positioningmentioning
confidence: 99%